A Descriptive Analysis of the Eastern Cape School Indicators - Ncanywa, T. (Africa's public service delivery & performance review, 2015)
This paper seeks to analyse the trends of education indicators that affect efficiency at schools in the Eastern Cape in the period 2009 to 2013. The focus is on the state of public ordinary schools which include primary and secondary schools from grade one to grade twelve. The province is regarded as a poor province as it constituted 95% of quintile one to three schools which are declared as ‘no fee schools’. There had been decline in learner performance as learners’ progress to higher grades and a drastic decline in important subjects such as Mathematics.  province had a significant number of educators with 16 years’ experience and an average of 45% under-qualified educators in 2013. There were variations in educator learner ratios per district with larger ratios found in the former Transkei. The province progressed well in learner transport, learner teacher support material and school nutrition programmes. There was no virtual change in infrastructural developments. Education in schools should be provided in a manner that ensures learners can realise their potential and aspirations, in schools that facilitate learning and reduce societal disparities.